Genomics-Enabled Novel Insight Into the Pathovar-Specific Population Structure of the Bacterial Leaf Streak Pathogen Xanthomonas translucens in Small Grain Cereals - Shah, Syed Mashab Ali; Khojasteh, Moein; Wang, Qi; Taghavi, S. Mohsen; Xu, Zhengyin; Khodaygan, Pejman; Zou, Lifang; Mohammadikhah, Sedighe; Chen, Gongyou; Osdaghi, Ebrahim (Frontiers in Microbiology, 2021)
The Gram-negative bacterium Xanthomonas translucens infects a wide range of gramineous plants with a notable impact on small grain cereals. However, genomics-informed intra-species population structure and virulence repertories of the pathogen have rarely been investigated. In this study, the complete genome sequences of seven X. translucens strains representing an entire set of genetic diversity of two pathovars X. translucens pv. undulosa and X. translucens pv. translucens is provided and compared with those of seven publicly available complete genomes of the pathogen. Organization of the 25 type III secretion system genes in all the 14 X. translucens strains was exactly the same, while TAL effector genes localized singly or in clusters across four loci in X. translucens pv. translucens and five to six loci in X. translucens pv. undulosa. Beside two previously-unreported endogenous plasmids in X. translucens pv. undulosa, and variations in repeat variable diresidue (RVD) of the 14 strains, tal1a of X. translucens pv. translucens strain XtKm8 encode the new RVDs HE and YI which have not previously been reported in xanthomonads. Further, a number of truncated tal genes were predicted among the 14 genomes lacking conserved BamHI site at N-terminus and SphI site at C-terminus. Our data have doubled the number of complete genomes of X. translucens clarifying the population structure and genomics of the pathogen to pave the way in the small grain cereals industry for disease resistance breeding in the 21st century’s agriculture.